2018
DOI: 10.1002/psb.1719
|View full text |Cite
|
Sign up to set email alerts
|

The Lancet Asthma Commission: treating children in primary care

Abstract: The Asthma Commission, published in The Lancet in September 2017, challenged current principles and called for a new approach to the diagnosis and treatment of asthma. Here, two of the Commission's authors discuss what primary care needs to know about their recommendations on the management of children with asthma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(9 citation statements)
references
References 20 publications
0
8
0
1
Order By: Relevance
“…Identification of the features of asthma and modifiable or treatable traits should only be the start of the diagnostic journey. 7 Asthma symptoms are normally intermittent in nature and may not be present at the time of clinical review, making the diagnosis challenging in some cases. 8 Additionally, disease phenotypes are not fixed and may evolve over time, necessitating ongoing review of symptoms and treatment.…”
Section: Presentation Of Asthmamentioning
confidence: 99%
See 3 more Smart Citations
“…Identification of the features of asthma and modifiable or treatable traits should only be the start of the diagnostic journey. 7 Asthma symptoms are normally intermittent in nature and may not be present at the time of clinical review, making the diagnosis challenging in some cases. 8 Additionally, disease phenotypes are not fixed and may evolve over time, necessitating ongoing review of symptoms and treatment.…”
Section: Presentation Of Asthmamentioning
confidence: 99%
“… 15 Typically, type 2-high asthma responds well to inhaled corticosteroid (ICS) treatment. 7 A number of biologic agents can be used in the management of asthma, under specialist supervision, and their use varies on asthma endotypes (table 8). 18 …”
Section: Paediatric Asthma Phenotypesmentioning
confidence: 99%
See 2 more Smart Citations
“…Asthma is a chronic inflammation of the airways and lungs. The Lancet Asthma Commission (Bush & Pavord, 2018) reported that asthma was an “umbrella term” for symptoms of wheeze, chest tightness, breathlessness, and coughing. Asthma is the most common chronic illness for youth, with a prevalence of about 10%, affecting over six million youth (Sullivan et al, 2018).…”
mentioning
confidence: 99%